2004
DOI: 10.1590/s0066-782x2004001600010
|View full text |Cite
|
Sign up to set email alerts
|

Terapia de células-tronco no infarto agudo do miocárdio, através de perfusão coronariana retrógrada: uma nova técnica

Abstract: 352Based on these observations, the hemodynamics team initiated the treatment of myocardial infarction with injection of bone marrow stem cells in a retrograde way through the coronary sinus. Case ReportThe patient is a 63-year-old, obese man with diabetes, hypertension, dyslipemia, and a positive familial history of coronary artery disease and previous myocardial infarction in the inferior wall 4 years earlier. Twelve days previously, the patient had an acute myocardial infarction in the anterior wall, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 8 publications
(5 reference statements)
0
3
0
1
Order By: Relevance
“…A via intramiocárdica de entrega de células em tecido cardíaco pode ser utilizada nos casos em que o emprego da via intracoronária é inadequado; no entanto, em decorrência de sua habilidade de entregar as células de modo seletivo nas regiões normais e peri-infartadas, eventos como extrassístoles e arritmia ventricular podem ser observados 13 . Recentemente, foi aventado o emprego da via retrógrada venosa como uma possível via de entrega de células 14 cães com peso aproximado de 25 kg (3 animais por grupo). Para a inclusão dos animais foram realizados exames bioquímicos séricos para alanina aminotransferase, creatina quinase fração MB (CK-MB), creatinina, hemograma, eletrocardiografia e ecocardiografia.…”
Section: Introductionunclassified
“…A via intramiocárdica de entrega de células em tecido cardíaco pode ser utilizada nos casos em que o emprego da via intracoronária é inadequado; no entanto, em decorrência de sua habilidade de entregar as células de modo seletivo nas regiões normais e peri-infartadas, eventos como extrassístoles e arritmia ventricular podem ser observados 13 . Recentemente, foi aventado o emprego da via retrógrada venosa como uma possível via de entrega de células 14 cães com peso aproximado de 25 kg (3 animais por grupo). Para a inclusão dos animais foram realizados exames bioquímicos séricos para alanina aminotransferase, creatina quinase fração MB (CK-MB), creatinina, hemograma, eletrocardiografia e ecocardiografia.…”
Section: Introductionunclassified
“…The intracoronary venous route, the retrograde coronary perfusion, is another important delivery method for stem cell therapy (Giordano, 2003;Murad-Netto et al, 2004). The coronary venous system was cannulated with a novel, investigational, double-balloon catheter.…”
Section: Intracoronary Vessel Infusionmentioning
confidence: 99%
“…This is particularly important because Janssens et al 5 found that half of patients undergoing autologous stem-cell transplant after AMI showed a microvascular obstruction pattern at the cardiac MRI, which may have impaired the migration of cells to cardiac tissue and hence, heart function improvement. Little is known about the retrograde percutaneous approach through the coronary vein, although this route has shown to be an effective way to deliver cells in animal human and models [6][7][8] . We suppose that the intravenous coronary (IVC) delivery can overcome the problem of MVO, because the diapedesis of circulating cells in the adjacent cardiac tissue occurs in the venous…”
mentioning
confidence: 99%